Scenarios and modeling of land use and cover changes in Portugal from 1980 to 2040 - Santos, Sara (2022)
Santos, S., Cabral, P., & Zamyatin, A. (2015). Scenarios and modeling of land use and cover changes in Portugal from 1980 to 2040. International Journal of Agricultural and Environmental Information Systems (IJAEIS), 6(4), 1-15. https://doi.org/10.4018/IJAEIS.2015100101